PENGARUH PEMBERIAN PAKAN HEWANI TERHADAP PERTUMBUHAN BELUT SAWAH (Monopterus albus) DALAM MEDIA AIR - Putra, Wiwin Kusuma Atmaja (Dinamika Maritim, 2015)
This research was done to investigate the growth rate and feed convertion ratio of Monopterus albus fed with various live foods in water medium. This research was done on June – July 2010 in Laboratory D3 Fisheries, Biology Faculty, UNSOED. The research was used experiment method based on Completely Randomized Designed with four treatment (Tubifex, cricket, yellow meal worm and pellet), and four repliacates. Data were analysed by ANOVA and the variables observed were absolute growth rate, specific growth rate, feed convertion ratio and survival rate. The results for the provision of tubifex worms, crickets, and the pellet was Tenebrio molitor is absolute growth rate of 7.48 ± 1.29 g, 4.52 ± 0.59 g, 5.08 g ± 1.37 and -0.62 ± 0, 79 g, specific growth rate of 0.18% ± 1.09, 0.75 ±0.08%, 0.76 ± 0.18% and -0.15 ± 0.16% , feed conversion ratio of 2.23 ± 0.21, 3.55 ± 0.54, 3.13 ± 0.4 and -6.37 ± 8.7 and survival rate of 91.68%, 95.83%, 83 , 35% and 95.83%. Water quality parameter for temperature 24–280C, water pH 6, Dissolved Oxygen 2,72–0,54 mg/L and ammonia 1,32–4,36 mg/L.